High-resolution structure of coexisting nanoscopic and microscopic lipid domains. Issue 9 (7th February 2017) - Belička, Michal; Weitzer, Anna; Pabst, Georg
Abstract : We studied coexisting micro- and nanoscopic liquid-ordered/liquid-disordered domains in fully hydrated multilamellar vesicles using small-angle X-ray scattering. Abstract : We studied coexisting micro- and nanoscopic liquid-ordered/liquid-disordered domains in fully hydrated multilamellar vesicles using small-angle X-ray scattering. Large domains exhibited long-range out-of-plane positional correlations of like domains, consistent with previous reports. In contrast, such correlations were absent in nanoscopic domains. Advancing a global analysis of the in situ data allowed us to gain a deep insight into the structural and elastic properties of the coexisting domains, including the partitioning of cholesterol in each domain. In agreement with a previous report, we found that the thickness mismatch between ordered and disordered domains decreased for nanoscopic domains. At the same time, we found also the lipid packing mismatch to be decreased for nano-domains, mainly due to the liquid-disordered domains becoming more densely packed when decreasing their size.